2021
DOI: 10.3390/bioengineering8110165
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Osteogenic Differentiation of Genetically Modified IL4 or PDGF-BB Over-Expressing and IL4-PDGF-BB Co-Over-Expressing Bone Marrow-Derived Mesenchymal Stromal Cells In Vitro

Abstract: The use of genetically modified (GM) mesenchymal stromal cells (MSCs) and preconditioned MSCs (pMSCs) may provide further opportunities to improve the outcome of core decompression (CD) for the treatment of early-stage osteonecrosis of the femoral head (ONFH). GM interleukin-4 (IL4) over-expressing MSCs (IL4-MSCs), platelet-derived growth factor (PDGF)-BB over-expressing MSCs (PDGF-BB-MSCs), and IL4-PDGF-BB co-over-expressing MSCs (IL4-PDGF-BB-MSCs) and their respective pMSCs were used in this in vitro study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…First, the results obtained using the current model in rabbits may differ from those in humans with ONFH 68 . Second, although we did not present in vitro data for the PDGF‐MSCs or IL‐4‐PDGF‐pMSCs in the current study, our previous in vitro reports using the same cells have demonstrated the efficacy of these MSCs 31 . Third, it is possible that the sample size was small in this study.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…First, the results obtained using the current model in rabbits may differ from those in humans with ONFH 68 . Second, although we did not present in vitro data for the PDGF‐MSCs or IL‐4‐PDGF‐pMSCs in the current study, our previous in vitro reports using the same cells have demonstrated the efficacy of these MSCs 31 . Third, it is possible that the sample size was small in this study.…”
Section: Discussionmentioning
confidence: 76%
“…Due to this early negative effect of IL‐4 on osteogenesis, we found that administration of IL‐4‐MSCs prevented osteogenesis in vivo 17 . Therefore, we created novel IL‐4‐PDGF‐MSCs and anticipated that PDGF‐BB from IL4‐PDGF‐pMSCs might overcome the potential negative effects of IL‐4 on bone formation and the initial inflammation required for it 31 . However, it was not observed in our results that PDGF‐BB could overcome the early negative effect of IL‐4 in vivo, explaining the inferior bone formation of the IL‐4‐PDGF‐pMSCs compared to the CD alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, PDGF-BB has beneficial immunomodulatory effects ( Zhang J. M. et al, 2016 ). Owing to the pleiotropy of PDGF-BB, some scholars have used it for the treatment of ONFH ( Tsubosaka et al, 2021 ). Guzman et al (2021) transduced MSCs with a lentiviral vector carrying the human PDGF-BB gene under the control of the phosphoglycerate (PGK) promoter and assessed the proliferative rate, PDGF-BB expression, and osteogenic differentiation capacity in vitro .…”
Section: Therapeutic Applications Of Growth Factors For Osteonecrosis...mentioning
confidence: 99%